How social media involvement affect consumer purchase intention on online social networking sites: examining the mediating role of self-disclosure - Wan, Li; Lan, Yuxi; Jian, Jie; Liu, Kehong (Frontiers in Communication, 2025)
IntroductionSocial media has a huge impact in marketing, as evidenced by the sheer number of users and the amount of time they spend on it each day. How online social networking sites (SNS) change shopping habits and even reshape the entire consumer market has become increasingly important topic in marketing field. Drawing upon the literature in user behavior, consumer purchase intention (CPI), and social media marketing, this research aims to investigate how social media involvement (i.e., make new friends, self-exhibition, enjoyment) affects CPI on online SNS and to examine the mediating role of self-disclosure in this relationship.MethodsThis study employs empirical regression analysis. Based on grounded coding results from interviews with 26 stakeholders, we developed measurement scales and collected 520 questionnaire responses. Using SPSS 21.0, we sequentially conducted reliability tests, correlation analyses, and regression modeling. Structural equation modeling via AMOS 26.0 was then employed to validate mediation pathways.ResultsThe main findings indicate that making new friends (β = 0.130, p < 0.05) and self-exhibition (β = 0.246, p < 0.001) on SNS positively affect CPI. Furthermore, the mediating role of self-disclosure (β = 0.168, p < 0.01) strengthens this relationship. The study presents an effective theoretical model illustrating the relationship between social media involvement and CPI.DiscussionThe results suggest that SNS managers can promote CPI by encouraging social media involvement within legal boundaries, while consumers should screen for credible merchants on SNS and protect their personal data.